Everyday Offending in Devonport Past and Present Session Two: Community Responses to Everyday Crime - Stevenson, Kim (Law, crime & history, 2023)
This witness seminar was organised by the University of Plymouth in association with the Institute for Contemporary British History, King’s College, London. The event was part of the Annual ESRC Research Festival in 2017 and was hosted by Real Ideas Organisation, Devonport. This transcription was subsequently organised by Culture and Heritage Exchange (CHEx). This second session of the Everyday Offending in Devonport Past and Present witness seminar had panellists from Hamoaze House (a local charity that offers rehabilitation facilities for families affected by the problematic use of drugs and/or alcohol), Shekinah Mission (a local charity that provides opportunities for people who are experiencing all forms of homelessness and other challenges), Real Ideas Organisation (support for individuals and communities in finding solutions to social problems), the Salvation Army (an evangelical Christian church who helps support poverty and homelessness in the community), and the Devonport Naval Heritage Centre (holds collection and hosts interactive experiences related to the relationships in Devonport between the Royal Navy and the people).